Interpersonal Communication Strategies for Counseling Teachers in Overcoming Student Delinquency at Nurul Falah High School Jakarta (Pena Cendekia Insani, 2023)
Interpersonal communication is communication that occurs between two or more people, who have a clear relationship, done face-to-face both verbally and non-verbally, with interpersonal communication will be able to affect the relationship between one another and connected in a certain way. Interpersonal communication is used by counseling guidance teachers in overcoming student delinquency at SMA Nurul Falah Jakarta. The purpose of this study was to determine the interpersonal communication strategies that were carried out between counseling guidance teachers and students in overcoming student delinquency at Nurul Falah High School Jakarta and to determine the inhibiting factors of the counseling counseling teacher's interpersonal communication process in overcoming student delinquency at Nurul Falah High School Jakarta.